2017
DOI: 10.1097/nmd.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Modified Electroconvulsive Therapy for Schizophrenia

Abstract: The underlying mechanism of modified electroconvulsive therapy (MECT) treatment for drug-resistant and catatonic schizophrenia remains unclear. Here, we aim to investigate whether MECT exerts its antipsychotic effects through elevating N-acetylaspartate (NAA) concentration measured by proton magnetic resonance spectroscopy (H-MRS). Multiple-voxel H-MRS was acquired in the bilateral prefrontal cortex (PFC) and thalamus to obtain measures of neurochemistry in 32 MECT, 34 atypical antipsychotic-treated schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Three studies examined the changes in brain metabolites using MRS ( Table 2 ). Two independent studies (n=34 and n= 10) revealed changes of N-acetyl-aspartate/creatinine (NAA/ Cr) ratio in the left PFC and the left thalamus [ 39 , 40 ]. Another study showed an increase in medial prefrontal γ-aminobutyric acid (GABA) levels (n=14) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies examined the changes in brain metabolites using MRS ( Table 2 ). Two independent studies (n=34 and n= 10) revealed changes of N-acetyl-aspartate/creatinine (NAA/ Cr) ratio in the left PFC and the left thalamus [ 39 , 40 ]. Another study showed an increase in medial prefrontal γ-aminobutyric acid (GABA) levels (n=14) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of costs attributed to inpatient care varied from country to country, depending on the organization of mental health services [ 5 ]. Regarding the cost composition, the non-medication treatment costs occupied the biggest proportion of inpatient costs for schizophrenia patients, which included modified electroconvulsive therapy [ 26 ], transcranial magnetic stimulation therapy [ 27 ], recreational therapy [ 28 ], individual psychotherapy [ 29 ], and group psychotherapy [ 30 ] during hospitalization. The medication costs were found to be the smallest part (10.9%) for inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging studies have shown an association of ECT in schizophrenia with increase in GM volume within the medial temporal lobe (amygdala, hippocampus, and insula) (45) and increased global functional connectivity density among key regions within default mode network (precuneus and medial prefrontal cortex) (46). ECT exerts therapeutic efficacy via elevating the concentration of N-acetylaspartate in the left prefrontal cortex and thalamus, indicating an antipsychotic effects through neuroprotective mechanism (47). In a sample of schizophrenia and depression, ECT reveals both disorder-specific and transdiagnostic effects.…”
Section: Discussionmentioning
confidence: 99%